Background Study for the National Strategy on Social Inclusion and Poverty Reduction, 2015-2020 - Tesliuc, Emil; Grigoras, Vlad; Stanculescu, Manuela (World Bank, Bucharest, 2016)
The background study for the national strategy on social inclusion and poverty reduction 2015-2020 was produced under a RAS agreement with the Ministry of Labor, Family, Social Protection, and Elderly of Romania. The report is a companion volume of the strategy, adopted by the Romanian Government in May 2015, and summarizes the diagnostics and analyses carried out by the World Bank team to provide a sound empirical base for the strategy. Given the multi-dimensional nature of poverty, the report includes diagnostics and policy recommendations on employment, social protection, education, health, housing, social participation, as well as regional and rural development policies. The document is based on a combination of desk research, qualitative data analysis, new data collected by the World Bank team and analyses of administrative, census, and survey data. This included qualitative research (for example, case-studies in two counties, interviews with representatives of central governmental bodies, interviews with recipients and eligible potential beneficiaries of means-tested benefits and with social workers), and quantitative data collection and analysis (a census on social housing stock; census of frontline social workers; a consolidated database of physicians, representatives of the pharmacies, community nurses, and health mediators; administrative dataset with social services for elderly, social services for people with disabilities and specialized child protection services; analysis of poverty. The book is organized in four parts. The first part starts with an analysis of the trends in poverty and social exclusion over the past few years and with a poverty forecast for the next five years (2015 to 2020). The second part analyzes the sectoral policies that must be implemented to tackle the problems identified in the first part of the volume. The third part turns its focus to area-based policies and discusses regional disparities, urban-rural differences, and specific problems in small towns and villages, rural, and urban marginalized areas, and Roma and non-Roma communities. The fourth part discusses the actions needed to strengthen the capacity of the public system to reduce poverty and increase social inclusion.